Antihypertensive treatment and adverse psychiatric reactions in primary health care - Emina Curic; Henrik Ohlsson; Kenneth Kendler; Jan Sundquist; Kristina Sundquist; Margareta Reis; Bengt Zöller (Journal of Human Hypertension, 2026)
Abstract Antihypertensive treatment (AHT) has been associated with adverse psychiatric reactions (APRs), but existing data are conflicting. The aim of the present study was to determine the risk for seven different APRs in drug-naive patients with newly diagnosed hypertension in primary health care. This cohort study analyzed registry data of individuals aged 40–70 with a newly diagnosed untreated hypertension without previous psychiatric or cardiovascular comorbidities in Swedish primary healthcare from 2006 and onwards. Adjusted Cox proportional hazard ratios (aHRs) with 95% confidence intervals (CIs) were estimated with seven different AHTs as time-dependent variables. Seven different APRs outcomes were studied. Bonferroni correction was used. Among 677,564 studied individuals (51% female, mean age [±standard deviation] 58.0 [ ± 7.7] years), the highest risks of APRs occurred within the first two years of AHT. All AHTs were associated with one or more APRs. Beta-blockers showed strongest associations with APR. During the first two years after diagnosis of hypertension, beta-blockers were significantly associated with substance abuse disorders (aHR=1.48, 95%CI 1.43-1.54), psychotic disorders (aHR=1.46, 95%CI 1.27-1.68), affective disorders (aHR=1.35, 95%CI 1.32-1.39), bipolar disorders (aHR=1.34, 95%CI 1.12-1.61), depressive disorders (aHR=1.36, 95%CI 1.32-1.40), anxiety disorders (aHR=1.51, 95%CI 1.48-1.54), and sleep disorders (aHR=1.27, 95%CI 1.24-1.30). Certain associations remained in a co-sibling analysis. AHTs are associated with several APRs especially during the first two years after diagnosis of hypertension. However, it is important to note that only association but not causality can be inferred due to persistent confounding that could not be practically adjusted for.